Clearing up uncertainties in graduate programs candidate selection using a data science approach - Costa, Evaldo B.; Raposo, Giselle; da S. Filho, Jose B.; Carvalho, Luiz Paulo; Vasconcellos, Wander dos S.; de Farias, Claudio Miceli (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS), 2020)
Brazilian Graduate Programs are evaluated by a specific foundation, CAPES. This evaluation qualifies the respective program with a grade, and this directly influences the permissions and funds assigned to this program, such as having a doctorate level, grading 4 or higher. One of the indicators is the student body, as an external variable outside the control of the program. Based on the Design Science Research methodology, we present a research on the construction of an artifact that clears up the selection of candidates for the programs, categorizing them according to the profiles of previous students, based on descriptive statistics and data analytics.